Ginkgetin promotes proliferation and migration of Schwann cells via PIGF/p38 MAPK signaling pathway. (December 2022) - Zhang, Yong; Niu, Yanfen; Weng, Qiuyan
Abstract: The proliferation and migration of Schwann cells is pivotal to peripheral nerve injury (PNI) repair. Recent studies have revealed that Ginkgetin has neuroprotective effects. Hence, we focused on identifying whether Ginkgetin could regulate the proliferation and migration of Schwann cells, thereby contributing to the repair of PNI. Rat Schwann cells RSC96 were treated with different concentrations of Ginkgetin. Short hairpin RNA targeting phosphatidylinositol glycan anchor biosynthesis class F (shPIGF) was employed to investigate the effects of PIGF on Ginkgetin-induced RSC96 cells. Viability of RSC96 cells was estimated via cell counting kit-8 (CCK-8) assay and proliferation of the cells was assessed by 5-ethynyl-2′-deoxyuridine (EdU) assay. Migration was estimated via wound healing assay and invasion was evaluated through transwell assay. Western blot was employed to test the expressions of PIGF, protein-38 (p38), and phosphorylated p-38 (p-p38). Ginkgetin (50 or 100 μg/ml) increased the viability, proliferation, migration, and invasion of RSC96 cells, up-regulated PIGF expression and raised the ratio of p-p38/p38, which were all reversed by PIGF silencing. Ginkgetin promotes proliferation, migration, and invasion of Schwann cells via PIGF/p38 MAPK signaling pathway. Highlights: Ginkgetin promoted proliferation, migration, and invasion of RSC96 cells. Ginkgetin up-regulated PIGF level and activated p38 MAPK signaling pathway. shPIGF reversed the effects of Ginkgetin on RSC96 cells.